Konsep Qath’iy-Zhanniy serta Implikasinya dalam Istinbath Hukum - Romli SA (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This article is the result of research that reviewing the concept qath'iy and zhanniy. In addition, also discussed how the existence of nash indicated (dilalah) by nash word. From the results of this study, the findings obtained are: first, that the concept qath'i and zhanniy as one of the devices in doing istinbath which rests on the principles of language is very useful in order to ensure legal charge indicated by nash word. Second, the concept of qath'iy and zhanniy also a means to ensure the existence of a proposition both in terms of existence of nash and also the dilalah. Knowing the existence (wurud) and nash of dilalah in reviewing Islamic law is a necessity. Third, the concept of qath'iy and zhanniy is a means to distinguish the clear and unclear text, because the nash of qath'iy or zhanniy each has it’s own characteristics that will influence and determine the conclusion of the legal charge indicated by the word. In addition, the concept of qath'iy and zhanniy also serves as a means for the development of Islamic law.